Elevated serum ferritin levels are associated with severity and prognosis of severe acute pancreatitis: a preliminary cohort study - Jie Wang; Qing-xie Liu; Dong-ling Teng; Yan-bing Ding; Guo-tao Lu; Wei-juan Gong; Qing-tian Zhu; Fei Han; Wei-ming Xiao (BMC Gastroenterology, 2022)
Abstract Background Serum ferritin (SF), as an acute-phase response protein, is used to reflect the degree of oxidative stress and systemic inflammatory responses. This study was designed to assess the effect of elevated SF levels on the severity of acute pancreatitis (AP). Methods From January 2013 to December 2020, 200 consecutive patients with AP were retrospectively reviewed to analyze the relationships among the etiologies of pancreatitis, the severity of the disease and SF levels. The receiver operating characteristic (ROC) curve and logistic regression analysis were used to assess whether elevated SF levels could predict the onset of organ failure in AP. Results 92 (46%) had high SF levels (> 275 ng/ml). SF levels were not associated with the etiology of AP disease. Among patients with high SF levels, there was a significant increase in the proportion of patients with severe AP (23.1% vs. 76.9%) and a higher proportion of systemic inflammatory response scores (25.9% vs. 44.6%) in comparison to patients with normal SF levels. The area under the ROC curve for SF in predicting persistent organ failure was 0.812 [95% confidence interval 0.721–0.904]. Conclusions F concentrations were positively correlated with the severity of AP, and quantitative assessment of SF can predict disease severity and organ failure in patients with AP.